Teaching video game design fundamentals : a guide for educating with practical examples and learning materials - Sandham, Andy, ....- (Boca Raton ; London : CRC Press, 2025)
"This comprehensive guide provides educators with everything they need to teach video game design fundamentals. With ready-made lesson plans, practical examples, assignment templates, exercises, video walkthroughs and learning materials in a modular format that allows for customization, it makes it easy to tailor lesson plans to meet the unique needs of your students, turning your classroom into an immersive learning environment that inspires creativity and innovation. The book offers a variety of exercises and learning materials to engage all types of learners, additionally with materials designed for different learning speeds that help them progress at a pace that suits them. With this book, you can ensure that all students have the opportunity to succeed and reach their full potential. This book will be vital reading to both educators teaching, and students learning, game design"--
Includes bibliographical references and index.
Keywords: Teachers; Video games